Informational frictions in the Brazilian health insurance market - Fonseca, Ricardo Barros de Aquino (2017)
I test for the existence of moral hazard and adverse selection in the Brazilian health insurance market. I use the positive correlation test, proposed by Chiappori and Salanié (2000), to assess the existence of asymmetric information in this market. I estimate the effect of health plan on treatment usage, controlling for many variables (measured blood pressure, age, smoker, etc.), identifying the effect of the plan. I use this coefficients as plan characteristics and estimate their effects on plan purchase using a simple logit regression. The coefficients from this estimation show the relative importance of anticipated moral hazard of different treatments on health plan choice. I find evidence of asymmetric information in the market for every state, in either the Metropolitan Area or not, and for the country as a whole. When performing the positive correlation test using hospitalizations as the usage variable, where moral hazard is assumed to be controlled, I find this evidence only for young women and for the last age group (59 years or more). I find no evidence of asymmetric information for plans paid through work, as expected. Several treatments are used more by people with plans, even when controlling for adverse selection. The analysis suggests that some of those are relevant for plan purchase.